Investigations of HCl influence on PVC dehydrochlorination (DHC) - German, K.; Kulesza, K. (Polimery, 2022)
The effects of several parameters such as polyethylene addition (12.6 wt. %), temperature (260-400degreesC) and dehydrochlorination (DHC) degree of the samples on the rate of PVC DHC process and on the time of HCl evolution, after freezing the reaction, have been investigated. Results of these investigations as well as the results of DSC and FT-IR measurements confirmed autocatalytic effect of HCl on DHC process. All experimental results are best explained by the hypothesis that DHC process is going on accordingly to the,conventional" mechanism [equation (4)]; HCl blocks also consequent reactions which stop the polyene sequence propagation [equation (5)].